2020
DOI: 10.1002/adfm.201910375
|View full text |Cite
|
Sign up to set email alerts
|

Electrode Design for Lithium–Sulfur Batteries: Problems and Solutions

Abstract: Pursuit of advanced batteries with high-energy density is one of the eternal goals for electrochemists. Over the past decades, lithium-sulfur batteries (LSBs) have gained world-wide popularity due to their high theoretical energy density and cost effectiveness. However, their road to the market is still full of thorns. Apart from the poor electronic conductivity of sulfur-based cathodes, LSBs involve special multielectron reaction mechanisms associated with active soluble lithium polysulfides intermediates. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
143
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(143 citation statements)
references
References 210 publications
(236 reference statements)
0
143
0
Order By: Relevance
“…In addition, carbon materials as S hosts offer enough conductive surface and abundant pores as ion/electron transport channels. [ 89 ] However, carbon–S (C–S) composites are plagued by issues such as low S utilization and large volume change. [ 90 ] To this end, enormous efforts have been made to design novel nanostructured C–S composite electrodes such as 3D hyperbranched hollow carbon nanorod/S, [ 91 ] hollow carbon sphere/S, [ 92 ] hollow carbon nanofiber or nanotube/S, [ 93 ] ordered meso‐/microporous core–shell carbon/S, [ 94 ] unstacked double‐layer‐templated graphene/S, [ 95 ] hollow graphene sphere/S, [ 96 ] interconnected CNTs/graphene nanosphere/S, [ 97 ] and tube‐in‐tube carbon/S nanocomposites.…”
Section: Optimization Strategies Of Redox Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, carbon materials as S hosts offer enough conductive surface and abundant pores as ion/electron transport channels. [ 89 ] However, carbon–S (C–S) composites are plagued by issues such as low S utilization and large volume change. [ 90 ] To this end, enormous efforts have been made to design novel nanostructured C–S composite electrodes such as 3D hyperbranched hollow carbon nanorod/S, [ 91 ] hollow carbon sphere/S, [ 92 ] hollow carbon nanofiber or nanotube/S, [ 93 ] ordered meso‐/microporous core–shell carbon/S, [ 94 ] unstacked double‐layer‐templated graphene/S, [ 95 ] hollow graphene sphere/S, [ 96 ] interconnected CNTs/graphene nanosphere/S, [ 97 ] and tube‐in‐tube carbon/S nanocomposites.…”
Section: Optimization Strategies Of Redox Reactionmentioning
confidence: 99%
“…To this end, the incorporation of conductive agents into S cathodes is proposed to improve the conductivity of the cathode materials. [ 89 ]…”
Section: Optimization Strategies Of Redox Reactionmentioning
confidence: 99%
“…Several manuscripts have successfully addressed the obstacles faced by Li–S cathodes through different and often complex chemical approaches ( Shaibani et al., 2020 ; Chong et al., 2018 ; Li et al., 2020 ; Huang et al., 2020 ). Additionally, scarce and toxic raw materials with potential supply chain bottleneck such as lithium, cobalt, vanadium or nickel are generally used in batteries, which increase their environmental impact ( Goodenough and Park, 2013 ; Olivetti et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the wide applications of lithium-ion batteries (LIBs) in portable electronics and electric vehicles, it is urgent to develop advanced battery systems with high energy density and power density. 1 7 The lithium–sulfur (Li–S) battery has emerged as one of the most promising candidates for next-generation energy storage systems, thanks to its high theoretical energy density of 2600 Wh kg –1 and the natural abundance of sulfur. 8 13 Recent studies demonstrated that the practical applications of the Li–S battery were severely plagued by its rapid capacity decay arising from the shuttling effect of lithium polysulfides (LiPSs), the intrinsic insulation of sulfur and its associated discharge products (Li 2 S 2 /Li 2 S), together with large volume variation and sluggish kinetics during the electrochemical cycling.…”
Section: Introductionmentioning
confidence: 99%